High performance benchmarking : 20 steps to success - Harrington, H. James; Harrington, James S. (New York : McGraw Hill Education, 1995)
The authors of this guide have actually "benchmarked" the process of benchmarking, delivering everything you need to know to get vastly better result.
Introduction to benchmarking -- The benchmarking overview -- The process of benchmarking -- Data collection and analysis -- Organizing for benchmarking -- The five phases of the benchmarking process -- Helpful hints for successful -- In conclusion
Includes bibliographical references and index.
Keywords: BENCHMARKING (MANAGEMENT)